THE ROLE OF BIOGENIC MATTER IN INCREASING THE PRODUCTIVITY OF CORN AND SORGO IN THE TERSKO-SULAK SUBPROVINCE CONDITIONS OF IRRIGATION - A. A. Aytemirov; M. B. Khalilov; T. F. Babaev; Z. G. Amiraliev (Юг России: экология, развитие, 2017)
Aim. The aim of the research is to substantiate the role of nutrients in increasing soil fertility which contribute to the growth of economic efficiency of the main spring corn crops for grain and grain sorghum in the linkages of crop rotation under conditions of irrigation of the Tersko-Sulak subprovince.Methods. Sampling of the soil and plants was carried out according to standard methods; statistical processing of yield data was carried out by the method of variance analysis using a standard method and computer program, thus based on the data obtained, the economic efficiency of the main spring corn crops for corn and grain sorghum was determined.Results. Studies (2015 - 2016) showed that the maximum net income was received during the growing season of corn for grain on options using a green mass of planting peas, amaranth, spring rapeseed, and winter wheat straw at the rate of 2 tons per hectare as well as mineral fertilizers of N150P75K75 treatment level, thus the net income amounted to 46.0 - 37.5 thousand rubles, respectively. While, with the cultivation of grain sorghum, the maximum net income was obtained on the variants of the green mass of amaranth, sowing peas, straw of winter wheat at the rate of 2 tons / ha, mineral fertilizers of N150P75K75 treatment level, thus the net income amounted to 58.9 - 44.1 thousand. rub. respectively.Conclusion. The cultivation of the main spring corn crops for grain and grain sorghum after the plowing of nutrients in the soil in the linkages of crop rotation under conditions of irrigation of the Tersko-Sulak subprovince proved to be profitable.